Fact-checking skills: a proposal for Communication studies - Herrero-Diz, Paula (2022)
The work of the journalist, on digital environments, needs a constant updating of the journalistic routines and process. Recently, phenomena like infodemic –an overabundance of information (both real and wrong information) regarding an issue- and disinformation –information under color of news that intends to mislead us- are manifestation of this situation; for example, in recent years, media newsrooms have focused their efforts not only on informing, but also on combating deceitful information published and spread with the intention of harming public opinion. This work has been named fact-checking journalism, that seems to require new talented journalists. This fact reveals the need of reviewing the competences that undergraduates acquire in the Communication degrees concretely and, additionally, in the Education degrees, because this is also a degree in which we find potential literacy educators in media. Thus, the present research aims at formulating the verification competences that allow students to acquire the skills and abilities needed in this task. For that purpose, the method of this study is based on expert judgement (N=18), whereby we asked for their assessment –using an ad hoc questionnaire- of the relevance of these competences and categories. The results show there are some concrete abilities and skills that require a new journalistic practice: the fact-checker journalist and, for that reason, study programs in Higher Education should include these new verification competencies in order to guarantee a teaching model in accordance with the new forms of practicing a discipline subjected to continuing changes.